Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s12917-020-02584-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular prevalence of emerging Anaplasma and Ehrlichia pathogens in apparently healthy dairy cattle in peri-urban Nairobi, Kenya

Abstract: Background Anaplasma and Ehrlichia species are tick-borne pathogens of both veterinary and public health importance. The current status of these pathogens, including emerging species such as Ehrlichia minasensis and Anaplasma platys, infecting cattle in Kenya, remain unclear, mainly because of limitation in the diagnostic techniques. Therefore, we investigated the Anaplasma and Ehrlichia species infecting dairy cattle in Nairobi, Kenya using molecular methods. Results A total of 306 whole blood samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 66 publications
3
25
2
Order By: Relevance
“…Matei et al [39] confirmed that dogs roaming rural communities in islands off the Kenyan coast were infected with A. platys. This study, however, found A. platys-like DNA in 16.9% of cattle in the study area, a prevalence notably higher than reported in cattle in China (4.35%) [40], Tunisia (3.5%) [41], Brazil (4.75%) [42], and Kenya [43]. However, as there was considerable sequence variation among A. platys clade sequences, our findings may represent an unknown diversity of A. platys-like pathogens circulating in the region as found in Tunisia [41].…”
Section: Discussioncontrasting
confidence: 87%
“…Matei et al [39] confirmed that dogs roaming rural communities in islands off the Kenyan coast were infected with A. platys. This study, however, found A. platys-like DNA in 16.9% of cattle in the study area, a prevalence notably higher than reported in cattle in China (4.35%) [40], Tunisia (3.5%) [41], Brazil (4.75%) [42], and Kenya [43]. However, as there was considerable sequence variation among A. platys clade sequences, our findings may represent an unknown diversity of A. platys-like pathogens circulating in the region as found in Tunisia [41].…”
Section: Discussioncontrasting
confidence: 87%
“…The application of the xMAP six-plex PCR assay to 455 field samples detected 30.1% (137/455) of positives, where amongst these positive samples we found 34.3% (11/32) cattle for A. marginale, 16.4% (59/358) dogs for A. platys, and 13.9% (50/358) dogs for E. canis. These results are consistent with prior published reports from other endemic regions for bovine anaplasmosis and canine rickettsial pathogens of the world, including the Caribbean region [62][63][64][65][66]. Co-infection with E. canis and A. platys in the Grenadian dog population was 1.1% (4/358) and this observation is also similar to previous reports from the Caribbean islands of St. Kitts and Republic of Haiti [67,68].…”
Section: Discussionsupporting
confidence: 92%
“…However, this rate is lower than that reported in Algeria (11.1%) ( 56 ), Pakistan (16.3%) ( 57 ), Morocco (21.9%) ( 58 ), and other regions from Tunisia (31.5%) ( 11 ). Compared with other studies from African countries, A. marginale prevalence rates were significantly higher in cattle from Zambia (47.9%) ( 59 ), Kenya (31–96.2%) ( 60 , 61 ), South Africa (60%) ( 62 ), Nigeria (75.9%) ( 63 ), and Madagascar (89.7%) ( 64 ). Indeed, these variations in A. marginale prevalence rate between the different countries and regions of the same country could be due to several factors, in particular the sampling seasons and bioclimatic zones, the type of used molecular assays and associated genes, the variation of incriminated arthropod vectors, the susceptibility of animal breeds, and/or other risk factors related to herd management ( 2 , 15 ).…”
Section: Discussioncontrasting
confidence: 62%